Dharma education and character development of students in retreat activities at Tri Ratna junior high school - Anggiyono Anggiyono; Burmansah Burmansah; Juni Suryanadi (International Journal of Science and Applied Science: Conference Series, 2025)
Character development is a major focus in education today as it shapes students' personalities. In the current era of globalization, where values of politeness are increasingly fragile, character development plays a vital role in defending the nation's identity and shaping a generation with good morals both in school and in society. Dharma Education is one of the means that can shape students' character, as explained by the moral values contained in Dharma Education, which include discipline, morality, and a sense of responsibility. This study aims to analyze and measure the level of influence of Dharma Education on student character development. This study uses a quantitative approach with a survey method. The subjects taken by the researcher were all ninth-grade students at Tri Ratna Junior High School, with a total of 45 respondents located in Taman Sari, West Jakarta. The instrument used was a questionnaire with a Likert scale. The data was analyzed using simple linear regression analysis. The results obtained showed that Dharma Education had a positive influence on student character development, especially in moral and ethical values, as well as in attitudes and responsibility. These findings have broad implications, ranging from the school environment to society as a whole. Based on the results of the research conducted by the researcher, it can be concluded that Dharma Education has a very high positive influence on student character development, especially in moral and ethical values, empathy, and responsibility. Dharma Education serves as an important foundation through retreat activities.